Guiding Questions Method and Extrinsic Learning Motivation of First Year University Students - Ermida Simanjuntak (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
The study aimed to examine the effects of guiding questions method on university students’ extrinsic motivation to study. The theory used was the ARCS model from Keller (1987) regarding extrinsic motivation to study. This study used a quasi-experimental method using a sample of 51 university students enrolled in General Psychology subject. Measurement used was an extrinsic motivation to study scale consisting of ARCS aspects which are attention, relevance, confidence, and satisfaction. Data was analysed using paired sample t-test and results showed that the guiding questions method was not effective to increase students’ extrinsic motivation to study. However, results also showed an increase in the ”satisfaction” aspect of extrinsic motivation to study following the guiding questions method.